Influence of the Effective Potential on the Crossover Width in the Two Flavor Polyakov-Nambu-Jona-Lasinio Model - Valbuena Ordóñez, Enrique; Mata Carrizal, Nallaly Berenice; Garza Aguirre, Adrián Jacob; Morones Ibarra, José Rubén (Hindawi Publ., 2020)
We study the strongly interacting matter phase diagram on the T − μ plane through the two flavor Polyakov extended NJL model. We compare the phase diagrams obtained from three different effective potentials, focusing on the behavior of the width of the crossover region and the critical end point for each case. We describe various susceptibilities to obtain the chiral crossover and the color deconfinement crossover.